h3 gourmet: not so fast food - Crespo de Carvalho, J. (2017)
The h3 case study focuses on the development and offer of a new chain of hamburger restaurants that began in Portugal and is spreading to other countries like Spain, Brazil and Poland. The general idea of the business venture is to grow quickly and occupy an unconventional place in the fast food burger business: a food chain with a gourmet touch, taking a high profile approach with natural ingredients, customization and quality service, where hamburgers are served on heated plates with cutlery and may be accompanied by a glass of wine, homemade lemonade or iced tea. The client can finish the meal with ice cream or chocolate coulant desserts with quality ingredients. H3 now has more than 40 restaurants; it is preparing to conquer the world and challenge the big players both in malls and street restaurants. Competitive advantages and critical success factors will play a vital role in this case.